Anti-phase boundary accelerated exsolution of nanoparticles in non-stoichiometric perovskite thin films - Hyeon Han; Yaolong Xing; Bumsu Park; Dmitry I. Bazhanov; Yeongrok Jin; John T. S. Irvine; Jaekwang Lee; Sang Ho Oh (Nature Communications, 2022)
Exsolution of transition metal cations from non-stoichiometric perovskites offer a route for the formation of stable nanoparticles on the surface. Here authors present an anti-phase boundaries-accelerated exsolution and two-step crystallisation of nanoparticles in non-stoichiometric perovskite thin films.